Heterotopias of History in the Modern Lithuanian Novel - Мержвинскайте, Бируте (Literatūra, 2016)
The paper focuses on the novel Mumbling Wall by Sigitas Parulskis which narrates the story of four generations of one family connected to the historical Lithuanian fortunes in the XX century. It considers the history as a conjunction of the two types of strategies – those of the story and those of the narrative. It examines how the novel inscribes the distrust of the great narratives, the absence of central perspective and the quotemanship that replace the history with the fragments of private partial stories, one of them representing the narrative about genesis of the readerly work. The analysis shows the way in which the anthropological skepticism, based on the conception of immutability and irrationality of affected human nature, the dependence on the outward authoritative relationship, the attention to the traumatic crisis situations or events together with autoreflection, the semantization of the problems of creativity, language and reference and the exposure of artistic devices are embodied in the metaphorical figure of the mumbling wall. The paper connects the polysemy of the central figure, which conjoins processuality and immobility, reality and fiction, visual and acoustic, with the concepts of heterotopia and heterochrony by Michel Foucault.
Keywords: history; narrative; heterotopias; Parulskis; mumbling wall; novel